2020
DOI: 10.1016/j.msard.2020.102186
|View full text |Cite
|
Sign up to set email alerts
|

BMI influences CD20 kinetics in multiple sclerosis patients treated with ocrelizumab

Abstract: Objectives: Ocrelizumab (OCR) is a humanized monoclonal antibody targeting CD20 antigen exposed on B cells surface. Kinetic of B-cells repopulation after depletion therapy shows high intra and inter-individual variability. The aim of this study was to explore the influence of Body Mass Index (BMI) on kinetic of B-cell repopulation after treatment with OCR and on treatment response. Methods: 108 Multiple Sclerosis (MS) patients were enrolled at the time of the first dose of OCR administration and prospectively … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
15
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 30 publications
(17 citation statements)
references
References 23 publications
2
15
0
Order By: Relevance
“…There was again evidence that baseline BMI was associated with CD19 re-population. For each increase in BMI of 5 units, the odds of having CD19 count above 1% of total lymphocyte count increased by 2.50 (95% confidence interval: 1.45-5.20; p=0.003) as suggested previously ( Kletzl et al, 2019 , Signoriello et al, 2020 ).…”
Section: Resultssupporting
confidence: 78%
“…There was again evidence that baseline BMI was associated with CD19 re-population. For each increase in BMI of 5 units, the odds of having CD19 count above 1% of total lymphocyte count increased by 2.50 (95% confidence interval: 1.45-5.20; p=0.003) as suggested previously ( Kletzl et al, 2019 , Signoriello et al, 2020 ).…”
Section: Resultssupporting
confidence: 78%
“…A recently published study observed a significant depletion of CD19 + cells after six months and one year of treatment, but an incomplete depletion was detected in 41.8% of patients and in 24% of patients a significant reappearance of this B cells (2%) has been achieved. ( 15 ) One of the factors that may be responsible for these variations in repopulation of CD19 + cells identified in this study is body mass index.…”
Section: Discussionmentioning
confidence: 71%
“…As found with rituximab, naive/mature B cell repopulation will coincide with CD19 repopulation [26,97] and would take a median 62-72 weeks after three [95% confidence interval (CI) = 59•7-73•0 weeks, n = 51] or four cycles (95% CI = 59•1-85•4, range = 27-175 weeks, n = 51), respectively [105]. Such levels would require monitoring, as there is marked variability in repopulation kinetics between individuals and is, in part, a product of the ocrelizumab fixed-dosing schedule, as it is clear that the intensity of B cell depletion and repopulation speed relates to the body mass index of the individual [106,107]. This suggests that dose-adjustment for weight may have some benefit, as currently used in the treatment of people with MS with oral cladribine [107].…”
Section: Repopulation Kinetics Of Ocrelizumabmentioning
confidence: 99%